Multidisciplinary Pain Management in Oncology: Balancing Opioid Use and Alternative Therapies - Tabin-Barczak, Wiktoria; Mazur, Michał; Waz, Dorota; Szarłowicz, Jakub; Goliszek, Zofia; Sobek, Karolina Łucja; Sokołowska, Aldona; Fikas, Klaudia; Chwaliszewski, Kamil; Samuła , Sebastian (Quality in Sport, 2025)
Introduction and purpose: Pain management in cancer patients remains a critical aspect of oncology care, significantly impacting quality of life and treatment outcomes. Despite advancements in cancer therapy, pain continues to be a prevalent and debilitating symptom, affecting up to 80% of patients with advanced cancer. This article aims to synthesize the latest evidence on the role of opioids in cancer pain management, focusing on their efficacy, safety, and factors influencing their use. It also explores the potential of multidisciplinary interventions and the contributions of nursing care in optimizing pain management. Materials and methods: A literature review was conducted, encompassing clinical trials, meta-analyses, and guidelines on cancer pain management. The review analyzed the mechanisms of cancer pain, opioid classification, pharmacokinetics and pharmacodynamics, as well as alternative pain management strategies, including non-opioid therapies and non-pharmacological interventions. Results: Opioids remain the cornerstone of cancer pain management, particularly for moderate to severe pain. However, their use is associated with risks such as constipation, nausea, respiratory depression, and potential immunosuppressive effects. Alternative therapies, including adjuvants and non-pharmacological interventions, play a crucial role in managing pain, especially in patients with neuropathic pain. Multidisciplinary team approaches have shown promise in improving pain control and patient QOL. Conclusion: Effective cancer pain management requires an individualized approach, integrating both pharmacological and non-pharmacological strategies. Further research is needed to optimize opioid use, develop novel therapies, and integrate digital technologies into pain management. Multidisciplinary collaboration and a holistic approach to patient care are essential for improving treatment outcomes.